Simulasi karakteristik mesin termoakustik pembangkit listrik dengan penambahan model kerugian minor dari dua segmen konis - Nurpatria, N.; Mirmanto, M.; Padang, Y.A.; Nurchayati, N. (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2024)
Acoustic energy output level from regenerator segment of a thermoacoustic engine model is attenuated along it’s loop due to several conditions including minor losses. This article discusses the result of Delta EC simulation of a thermoacoustic engine model acting as simple electric power generator that inserted with two conical segments. The cone segments are capable to lower the energy loss which in turn improve the overall performance of the engine in term of nett heat to acoustic energy conversion efficiency. Combined acoustic energy loss induced by both cones is equivalent to 4.94 watts minor losses. At this condition, regenerator segment amplifies the incoming acoustic energy flow of 57.02 watt up to 93.57 watt, which is equals to 36.55 watts acoustic amplification. It leads to increasing of overall engines heat to acoustic efficiency into 14.05%, which is 1.29% higher than those at the case of without cones. This engine performance improvement addressed to smoother streamline of working fluid flow inside the loop.